Printing 1D Assembly Array of Single Particle Resolution for Magnetosensing. Issue 19 (25th March 2018) - Gao, Meng; Kuang, Minxuan; Li, Lihong; Liu, Meijin; Wang, Libin; Song, Yanlin
Abstract: Magnetosensing is a ubiquitous ability for many organism species in nature. 1D assembly, especially that arranged in single‐particle‐resolution regulation, is able to sense the direction of magnetic field depending on the enhanced dipolar interaction in the linear orientation. Inspired by the magnetosome structure in magnetotactic bacteria, a 1D assembly array of single particle resolution with controlled length and well‐behaved configuration is prepared via inkjet printing method assisted with magnetic guiding. In the fabrication process, chains in a "tip‐to‐tip" regulation with the desired number of particles are prepared in a confined tiny inkjet‐printed droplet. By adjusting the receding angle of the substrate, the assembled 1D morphology is kept/deteriorated depending on the pinning/depinning behavior during ink evaporation, which leads to the formation of well‐behaved 1D assembly/aggregated dot assembly. Owing to the high‐aspect‐ratio characteristic of the assembled structure, the as‐prepared 1D arrays can be used for magnetic field sensing with anisotropic magnetization M // / M ⊥ up to 6.03. Abstract : A 1D assembly array of single particle resolution is prepared via inkjet printing method under magnetic guiding. In the confined tiny printed droplet, particles are attracted "tip‐to‐tip" into 1D assembly, which pins on the substrate with low receding angle. Inspired by the magnetosome structure, the as‐prepared 1D array can be used for magnetic field sensing with anisotropic magnetization M // / M ⊥ up to 6.03.